2022
DOI: 10.1111/jbi.14328
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of environmental filtering and dispersal limitation on the species assemblage of the Tibetan Plateau

Abstract: Aim: Mountains harbour a rich and non-random cluster of species, yet knowledge of the species' biological attributes that support their coexistence in the montane community is limited. Here, we investigated the association of species occurrence on the Tibetan Plateau with their morphological, ecological or evolutionary constraints. Location: Tibetan Plateau (TP).Taxon: Mammals and birds. Methods:We tested whether species occurrence on the TP correlates with morphological, ecological or evolutionary constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 81 publications
3
10
0
Order By: Relevance
“…In the subsidence lake during summer, the contribution of the deterministic mechanisms on impacting the bacterial community was small, demonstrating that the stochastic mechanisms were more crucial (Figure 5B). This was consistent with what had been found in previous plateau lakes, which found that the increased temperature in summer promoted microbial metabolic rates, thereby increasing the randomness of speciation and death (He et al, 2022). Concurrently, the increasing relative importance of stochastic processes in summer was well associated with higher nutrient contents.…”
Section: Communities Structure and Assembly Mechanisms Of Bacterial I...supporting
confidence: 91%
See 2 more Smart Citations
“…In the subsidence lake during summer, the contribution of the deterministic mechanisms on impacting the bacterial community was small, demonstrating that the stochastic mechanisms were more crucial (Figure 5B). This was consistent with what had been found in previous plateau lakes, which found that the increased temperature in summer promoted microbial metabolic rates, thereby increasing the randomness of speciation and death (He et al, 2022). Concurrently, the increasing relative importance of stochastic processes in summer was well associated with higher nutrient contents.…”
Section: Communities Structure and Assembly Mechanisms Of Bacterial I...supporting
confidence: 91%
“…Among the winter and summer, bacterial community similarity exhibited a strong and significant relationship with physicochemical parameters (r = 0.65, p < 0.001; Supplementary Figure S4), and T explained 18.26% of the total community variations solely (Figure 4A), which is evidence for environmental filtering. The environmental stress on the temperature may boost the filtering out of communities with weak cold resistance and narrow niche breadth in winter (He et al, 2022). However, warm weather conditions were conducive to the growth of species and the maintenance of biodiversity (Wang et al, 2022b).…”
Section: Communities Structure and Assembly Mechanisms Of Bacterial I...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since it is the evolutionary history and functional traits that dominate the interactions between species, and between species and ecosystem functioning (Lavorel & Garnier, 2002; Mouchet et al, 2010; Webb, 2000), using species functional and phylogenetic structures to explore the maintenance of biodiversity is considered to be more reliable and “predictive” (Veron et al, 2019; Zakharova et al, 2019). Following this claim, an increasing number of ecologists started to explore the mechanisms of community assembly in different taxa and regions by using a combination of species’ functional and phylogenetic characteristics (He et al, 2022; Jarzyna et al, 2021; Montaño‐Centellas et al, 2021). However, these studies were concentrated on plants (Li et al, 2022; Xu et al, 2017; Zhang et al, 2021), birds (Du et al, 2021; Hanz et al, 2019) and small mammals (Kohli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mountains play an important role in regional riverine ecosystems ( Viviroli et al 2007 , Anderson and Goulden 2011 ) and the formation of their biota is more sensitive than that of other areas to geological history ( Tang et al 2009 , He et al 2022 ). Mountain ecosystems, such as the QTP, characterised by the largest quantity of glaciers and known as the water tower of Asia, are the regions of origin and maintenance of a substantial fraction of rivers and plateau lakes ( Immerzeel et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%